FGF signaling in mammary gland fibroblasts regulates multiple fibroblast functions and mammary epithelial morphogenesis - Sumbal, Jakub; Koledova, Zuzana (Development, 2019)
Fibroblast growth factor (FGF) signaling is crucial for mammary gland development. Although multiple roles for FGF signaling in the epithelium have been described, the function of FGF signaling in mammary stroma has not been elucidated. In this study, we investigated FGF signaling in mammary fibroblasts. We found that murine mammary fibroblasts express FGF receptors FGFR1 and FGFR2 and respond to FGF ligands. In particular, FGF2 and FGF9 induce sustained ERK1/2 signaling and promote fibroblast proliferation and migration in 2D cultures. Intriguingly, only FGF2 induces fibroblast migration in 3D extracellular matrix (ECM) through regulation of actomyosin cytoskeleton and promotes force-mediated collagen remodeling by mammary fibroblasts. Moreover, FGF2 regulates production of ECM proteins by mammary fibroblasts, including collagens, fibronectin, osteopontin and matrix metalloproteinases. Finally, using organotypic 3D co-cultures we show that FGF2 and FGF9 signaling in mammary fibroblasts enhances fibroblast-induced branching of mammary epithelium by modulating paracrine signaling, and that knockdown of Fgfr1 and Fgfr2 in mammary fibroblasts reduces branching of mammary epithelium. Our results demonstrate a pleiotropic role for FGF signaling in mammary fibroblasts, with implications for regulation of mammary stromal functions and epithelial branching morphogenesis.
Keywords: Animals; MAP Kinase Signaling System; Receptor, Fibroblast Growth Factor, Type 2; Paracrine Communication; Female; parakrinní signalizace; Fibroblast Growth Factor 9; ženské pohlaví; Fibroblasts; Fibroblast Growth Factor 2; receptor fibroblastových růstových faktorů, typ 2; fibroblastový růstový faktor 9; Mice; fibroblasty; fibroblastový růstový faktor 2; myši; Mammary Glands, Animal; mléčné žlázy zvířat; Mice, Inbred ICR; myši inbrední ICR; Receptor, Fibroblast Growth Factor, Type 1; zvířata; receptor fibroblastových růstových faktorů, typ 1; MAP kinasový signální systém